Kritik Sosial dalam buku Republik #Jancukers - Nanda riski Ardhana (STKIP PGRI Jombang, 2015)
Social criticism is a form of communication in society that aims or functions as a control over the course of a social system or community process. According to Marbun, social criticism is a phrase that consists of two words, namely criticism and social. The use of qualitative methods in this research is descriptive, while the object of research is the book of the Republic of Jancukers by Sujiwo Tejo. The data in this study are quotes from the Republic of Jancukers books which are included in the form of Analysis and qualitative.Based on the results of the data analysis, it was found that the nature of the Republican book J # ncukers contains unique and unique insinuations towards the people, the government and even us as connoisseurs of this book. Sujiwo Tejo in this J # ncukers Republican book.The foresight of the people in measuring a discourse is different, there are those who think the satire of government patterns and policies is anti-government, some think that it is a form of love for the government, because they still care. When speaking politeness and sin, it is only regional. For example, the word Jancuk is only understood by the people of East Java but is not understood by the people of Irian Jaya and the word actually has an interesting history and meaning.